Mitigating browning and improving texture issues in persimmons: the impact of freezing pretreatment on vacuum microwave drying - Tang, Xiaoxian; Zhao, Min; Ren, Aiqing; Duan, Zhenhua; Liu, Yan; Xian, Zhaokun (Frontiers in Sustainable Food Systems, 2025)
IntroductionVacuum-microwave drying (VMD) can lead to undesirable effects in persimmons, such as browning, charring, surface wrinkling, and structural collapse, all of which significantly reduce product quality.MethodsThis study proposed and evaluated a freezing pretreatment at an optimized temperature of −80°C prior to VMD. Persimmon slices with and without pretreatment were assessed in terms of appearance, physical properties, processing and quality indicators, sensory texture characteristics, and pore structure.ResultsThe freezing pretreatment improved color uniformity by 64.5% and reduced the browning index growth rate by 21.4%. It also increased expansion rate and rehydration capacity by 15.7% and 21.5%, respectively. In terms of texture, hardness and chewiness decreased by 84.4% and 91.6%, while crispness improved by 40.4%.DiscussionIntegrating freezing pretreatment with VMD effectively mitigates browning and texture degradation in persimmons. These results demonstrate a promising approach for producing high-quality persimmon crisps. Future studies should explore the optimal freezing duration and temperature, and assess the applicability of this method to other fruits and vegetables.